2021
DOI: 10.1139/cjfr-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of coastal Douglas-fir and western redcedar in response to species mixture, planting density, and soil carbon:nitrogen ratio

Abstract: Mixed-species plantations have been suggested as ecologically and economically viable alternatives to monocultures. We examined the growth response of coastal Douglas-fir (Pseudotsuga menziesii var. menziesii (Mirb.) Franco) and western redcedar (Thuja plicata Donn ex D. Don in Lamb.) to different species mixtures (Douglas-fir : western redcedar mixtures of 1:0, 1:1, 1:3, and 0:1) and planting densities (500, 1000, and 1500 stems·ha−1) in a dry maritime forest on eastern Vancouver Island, Canada. Twenty-two ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The result is a decrease in tree biomass production as the amount of nitrogen available to the seedlings for photosynthetic activity (leaf area and chlorophyll) and subsequent growth (height, diameter, and biomass) decreases. These results coincide with studies that have found that tree height, DBH and biomass are negatively impacted when there is an increase in the soil C:N ratio [38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“…The result is a decrease in tree biomass production as the amount of nitrogen available to the seedlings for photosynthetic activity (leaf area and chlorophyll) and subsequent growth (height, diameter, and biomass) decreases. These results coincide with studies that have found that tree height, DBH and biomass are negatively impacted when there is an increase in the soil C:N ratio [38][39][40].…”
Section: Discussionsupporting
confidence: 91%
“…Because trees grow differently depending on life history strategy (Hara et al, 1991;Messier et al, 1999;Omari et al, 2021), height does not capture all the elements of a big-treed forest (e.g., some of BC's massively wide western redcedars are relatively short); hence, we investigated secondary attributes, including diameter and volume metrics, to build a more nuanced model of old forest structure (Burrascano et al, 2013). Available attributes, however, were poorly related to measured values for a given stand, and adding diameter did not improve the relationship between estimated and measured tree size.…”
Section: Evaluating Indicator Reliabilitymentioning
confidence: 99%